Interictal Electroencephalogram and MRI of Brain in the Localization of Focal Epilepsy: An Observational Study in a Tertiary Care Hospital (Bangladesh Journal of Neuroscience, 2026)
Background: Focal epilepsy is commonly associated with focal epileptogenic lesions and identification of these lesions are vital for management. Electroencephalogram (EEG) and Magnetic Resonance Imaging (MRI) of brain are commonly used neurodiagnostic procedures to localize the lesions.Objective: The study aims to observe the diagnostic yields of interictal EEG and MRI of the brain in the localization of focal epilepsy.Materials and Methods: This cross-sectional study was carried out in the Department of Neurology at National Institute of Neurosciences & Hospital (NINS&H), Dhaka from January, 2021 to June, 2022. A total number of 105 focal epilepsy patients were included in this study based on inclusion and exclusion criteria with ages above 12 years of both sex. Detailed history, clinical examination, EEG and MRI evaluation were done and recorded. Chi-Square test was performed to compare the EEG and MRI data and p value of